Macroconcept Army: Analyzing the Structure of a Borrowed Macroconcept - A. B. Bodrikov (Kemerovo State University, 2021)
The research objective was to describe the structure of the borrowed macroconcept army, i.e. to determine its motivating and concept signs in the Russian mentality. The study involved nine etymological dictionaries and revealed six motivating signs, while nine explanatory dictionaries and language material made it possible to identify 32 conceptual signs: 1. Types and kinds of military units (eleven signs): air; (field) troops; armed (motivating signs to arm); (highest military / large) unit; naval; as opposed to naval and air forces; opposite of the elite military units; one / different branches of the armed forces; missile; ground (infantry / cavalry); without privileges. 2. Armed people (seven signs): Bolshevik (military forces) / Red Army; (military) men; army; aggregate; forces; composition of (several) corps and divisions; part of the active armed forces (at the front). 3. Purpose (six signs): war; to make capable of fighting (motivating signs); for conducting military operations; protection (of the state); ensuring the inviolability of borders and independence of the state; service. 4. Combat equipment (four signs): weapon (motivating signs); device (motivating signs); supply (motivating signs); to equip (motivating signs). 5. Leadership (two signs): state; under the general command of the chief military leader. 6. Association of people on a certain basis (two signs): a large number of people (united by a common feature: profession, social status, the same problem); proletariat / workers / workers.